KRITIK SASTRA ARAB TRANSFORMATIF DAN PEMBELAJARANNYA: PENGARUSUTAMAAN FEMINISME POSTMODERN BERBASIS HEUTAGOGIS - Muhammad Rusydi; Suhadi Suhadi; Awaliah Musgamy (AN-NISA, 2023)
Abstract: The presence of transformative Arabic literary criticism learning can provide a forum for language reinforcement as a gender-responsive value transformation medium. In this process, transformative Arabic literary criticism can provide a model for how the various roles of language as a text can be transformed to reinforce the role of women who have been trapped in gender-unresponsive stereotypes. Learning transformative Arabic literary criticism as a forum for mainstreaming heutagogic-based postmodern feminism is an alternative value transformation in the world of education. In this effort, there are several strategies that can be done which in this case are, 1) enrichment of gender-responsive heutagogic-based scientific literature in transformative Arabic literary criticism, 2) strengthening the paradigm of heutagogic-based postmodern feminism studies in transformative Arabic literary criticism, 3) and opening access to mainstreaming the results of heutagogic-based postmodern feminism studies in various dimensions of social life. The presence of transformative Arabic literary criticism learning can provide a forum for language reinforcement as a gender-responsive value transformation medium.Keywords: Arabic Literary, Postmodern Feminism, HeutagogicAbstrak: Hadirnya pembelajaran kritik sastra Arab transformatif dapat memberikan wadah penguatan bahasa sebagai media transformasi nilai yang responsif gender. Dalam proses tersebut, kritik sastra Arab transformatif dapat memberikan suatu model bagaimana berbagai peran bahasa sebagai sebuah teks dapat ditransformasikan untuk menguatkan peran perempuan yang selama ini banyak terjebak pada sterotip yang tidak responsif gender. Pembelajaran kritik sastra Arab transformatif sebagai wadah pengarusutamaan feminisme postmodern berbasis heutagogis merupakan suatu alternatif transformasi nilai dalam dunia pendidikan. Dalam upaya tersebut, ada beberapa strategi yang dapat dilakukan yang dalam hal ini adalah, 1) pengayaan literatur keilmuan berbasis heutagogis yang responsif gender dalam kritik sastra Arab transformatif, 2) penguatan paradigma kajian feminisme postmodern berbasis heutagogis dalam kritik sastra Arab transformatif, 3) serta pembukaan akses pengarusutamaan hasil kajian feminisme postmodern berbasis heutagogis dalam berbagai dimensi kehidupan sosial. Kata Kunci: Sastra Arab, Feminisme Postmodern, Heutagogis